Tampering with freedom - The Independent (Asia Pacific Network, 1996)
"Today is the beginning of a seminar in Port Moresby which will look at media freedom and accountability, to determine whether changes need to be made to ensure that, while freedom of the press is maintained, owners, editors, and journalists of all elements of the media are accountable and that persons aggrieved by media abuses have accessible redress. Is there a real justification for this move? Can the people of this country be guaranteed that such a move will not deviate from its original intention?"